Kualitas cracker cibi sebagai alternatif cemilan sehat - Fitri Yani Arbie; Novian Swasono Hadi; Denny Indra Setiawan; Rahma Labatjo; M Anas Anasiru (AcTion: Aceh Nutrition Journal, 2020)
Non-Communicable Diseases (NCD) is the leading cause of death globally. One recommended strategy for improving food quality in preventing obesity and NCD is fish consumption. The selection of biscuit products "Cibi" aims as an effort to prevent PTM through food diversification. In addition to developing healthy, economical and nutritious cracker products. Objective, to obtain the nutritional content of biscuits with the substitution of mackerel flour and corn flour as an alternative to complementary feeding in efforts to prevent non-communicable diseases. Methods, laboratory experimental methods using panelists to test the acceptability of food. Homogeneity Test, Anova Test and Tuckey Advanced Test to see the difference in the best treatment. Results, the most preferred cibi crackers formula from the aspect of color, taste, and crispness assessment is the F2 formulation and contains higher water, protein, iron and zinc content compared to the control formula. However, in terms of ash, fat and carbohydrate content, Formulation F2 is lower than the control formula. Conclusion, the most preferred cibi crackers formula from the aspect of taste, color, and crispness evaluation is the F2 formulation, which is a formula with 25 gram of mackerel fish flour and 25gram sweet corn flour. The results of the AKK Test (Yeast Mold Figures) show that F3 still has Yeast and is still within the safe limits of SNI Biscuits. Penyakit Tidak Menular (PTM) menjadi penyebab utama kematian secara global. Salah satu strategi yang direkomendasikan untuk meningkatkan kualitas makanan dalam pencegahan obesitas dan PTM adalah konsumsi ikan. Pemilihan produk biscuit “Cibi” bertujuan sebagai upaya pencegahan PTM melalui diversifikas pangan. Selain itu untuk mengembangkan produk cracker sehat, ekonomis dan bergizi sebagai alternative MP-ASI pada usia di atas 1 tahun. Penelitian bertujuan untuk memperoleh kandungan zat gizi biskuit dengan subtitusi tepung ikan kembung dan tepung jagung sebagai alternatif MP-ASI dalam upaya pencegahan penyakit tidak menular. Penelitian menggunakan metode eksperimen laboratorium dengan melibatkan panelis untuk menguji daya terima makanan. Uji Homogenitas, Uji Anova dan Uji Lanjut Tuckey untuk melihat perbedaan perlakuan terbaik. Hasil, formula crackers Cibi yang paling disukai dari aspek penilaian warna, rasa, dan kerenyahan adalah formulasi F2 dan mengandung kadar air, protein, besi dan seng yang lebih tinggi dibandingkan dengan formula kontrol. Namun, dari segi kadar abu, lemak dan karbohidrat, Formulasi F2 lebih rendah dibandingkan dengan formula kontrol. Kesimpulan, formula crackers Cibi yang paling disukai dari aspek penilaian rasa, warna, dan kerenyahan adalah formulasi F2, yaitu formula dengan substitusi tepung ikan kembung 25 gram dan tepung jagung manis 25 gram. Hasil Uji AKK (Angka Kapang Khamir) menunjukkan F3 masih terdapat Khamir dan masih berada pada batas aman SNI Biskuit.